RF components and circuits - Carr, Joseph J. (Newnes, 2002)
Some basic knowledge of electronics is assumed, but the essential features of RF are fully described, including the important topic of receiver dynamic which is often overlooked in basic textbooks. The theory and circuit descriptions are geared towards genuine design applications rather than the oversimiplifications and skeleton circuits of many college texts. During his career, the late Joe Carr was one of the world's leading writers on electronics and radio, and an authority on the design and use of RF systems. Whether you are looking for a complete self-study course in RF technology, or a concise reference text to dip into, this book has the solution. A complete course in understanding and designing RF circuits Practical design knowhow from a world-class author.